Legal Implications of Drug Use for Professional Athletes on Employment Contracts and Organizational Sanctions - Rochmadi Rochmadi; Indah Kusuma Wardhani (Siber Nusantara of Law and Politic Review, 2026)
The phenomenon of professional athletes' involvement in drug abuse cases raises complex legal issues due to the multi-layered legal consequences of various legal regimes. Athletes not only face national criminal law as stipulated in Law Number 35 of 2009 concerning Narcotics, but also face contract-based civil sanctions and sanctions from sports organizations subject to lex sportiva. This situation creates tension between the rehabilitative approach adopted by criminal law towards drug abusers and the repressive and reputational disciplinary approach in the sports legal system. The accumulation of these sanctions has the potential to give rise to over-penalization practices that threaten the principles of substantive justice, legal certainty, and the sustainability of professional athletes' careers. This study aims to analyze the legal status of professional athletes within the criminal, civil, and sports organizational legal regimes, and examine the normative conflicts arising from the application of multiple sanctions for the same act. The research method used is normative legal research with a statutory, conceptual, and limited comparative approach to lex sportiva practices and Court of Arbitration for Sport decisions. The research findings reveal a conflict in law enforcement objectives across regimes, which affects the legal protection of athletes. This study proposes a reconstruction of the legal protection model for professional athletes through regulatory harmonization, the application of the principle of proportionality, and the strengthening of a rehabilitative approach that maintains the integrity of sport and the public interest.